A Cointegration Model for Search Equilibrium Wage Formation. (IMF Working Papers; Working Paper, 2004)
In flow models of the labor market, wages are determined by negotiations between workers and employers on the surplus value of a realized match. From this perspective, this paper presents an econometric analysis of the influence of labor market flows on wage formation as an alternative to the traditional specification of wage equations in which unemployment represents Phillipscurve or wage-curve effects. The paper estimates a dynamic wage equation for the Netherlands using a cointegration approach. It finds that labor flows, and notably flows from outside the labor market, are important determinants of both short-run and long-run wage setting.